Sakura and Shifting Tides: Exploring the Deskilling and Upskilling Experiences of Indonesian Nurses in Post-COVID-19 Japan - Ria Utami Panjaitan; Achir Yani S Hamid; Wako Asato; Yudi Ariesta Chandra; Andrio Adibowo Muktiwibowo; Henny Permatasari; Mohamad Yusup; Azimatul Aliyah (Talenta Publisher, 2026)
This qualitative study explored the deskilling and upskilling experiences of Indonesian nurses working in Japan during the post-COVID-19 period, with particular relevance on professional adaptation and evolving health system needs and labor demands. An exploratory qualitative design was adopted with 41 Indonesian nurses providing care in hospitals and long-term care facilities in Chiba, Meguro, Saitama and Yokohama. Data were collected during 2023 through face-to-face semi-structured interviews. Data were analysed using Braun and Clarke's six-phase inductive thematic analysis. The analysis generated seven interrelated themes: (1) deskilling experiences, (2) upskilling and reskilling strategies, (3) post-COVID-19 workplace changes, (4) bilateral cooperation dynamics, (5) cultural and professional adaptation, (6) career transition planning, and (7) perceived benefits of working in Japan. Deskilling emerged as a dominant issue, driven by occupational downgrading, restricted clinical practice, and regulatory barriers. Yet people put into action adaptive behaviours such as: informal learning; training attendance and skill reconstruction attempts. Deskilling thus appears not as a simple linear decline but rather as a hybrid phenomenon influenced both by structural factors linked to business performance and individual actions connected to the nature of work itself. These have policy implications for the design of clinical bridging programs, with structured pre-departure preparation in Japan integrated with medical Japanese language training; clinical skill maintenance under supervision in host institutions; and re-licensure pathways for returnee Indonesian nurses. Keyword: Deskilling; Upskilling; Migrant Nurses; Career Transition; Post-COVID-19; Japan–Indonesia Cooperation